Sex differences in Life's Essential Eight and its Association with mortality among US adults without known cardiovascular disease - Gurleen Kaur; Ofer Kobo; Purvi Parwani; Alaide Chieffo; Martha Gulati; Mamas A. Mamas (Elsevier, 2024)
Background: The American Heart Association's (AHA) Life's Essential 8 (LE8) score is a helpful tool to quantify cardiovascular health (CVH) metrics. We sought to assess sex differences in relation to LE8 and its components along with association with mortality. Methods: The National Health and Nutrition Examination Survey (NHANES) between 2009 and 2018 was utilized to evaluate the prevalence of health metrics included in LE8 among adult participants > age 18, stratified by sex. We categorized overall CVH, health factors, and health behaviors into 3 levels (low: <50, moderate: 50 -79, high: ≥80) following the AHA's algorithm. Health metrics were further subdivided into health behaviors (diet, physical activity, nicotine exposure, and sleep) and health factors (body mass index, non-high density lipoprotein cholesterol, blood glucose, and blood pressure). LE8 scores were also evaluated based on age, race/ethnicity, and socioeconomic status. Cox proportional hazard models were used to evaluate the association between the levels of CVH and risk of all-cause and cardiovascular mortality, with adjustment for age group and race. Results: Among 22,761 participants, 52 % were female. Overall CVH score was similar in both females and males (65.8 vs. 65.9). Females had higher health factors score (64.3 vs. 63.1, p < 0.001) and lower health behaviors score (67.2 vs 68.6, p < 0.001). Amongst individual metrics, blood pressure score was higher in females (73.2 vs. 67.7, p < 0.001) while males had higher physical activity score (70.6 vs. 54.9, p < 0.001). For individuals under 65 years of age, overall CVH and health factors scores were higher in females while in those age 65 or older, males had higher scores. The most prominent sex differences were noted in non-Hispanic Black females who had significantly lower CVH scores than Black males (62.6 vs. 74.7, respectively, p < 0.001. High LE8 scores vs. low LE8 scores demonstrated lower all-cause (HR 0.37 vs 0.35) and CV mortality (HR 0.35 vs. 0.36) in both males and females, respectively (p-interaction 0.21 and 0.28). High health behaviors scores also demonstrated a significant association with lower all-cause (0.34 vs. 0.24) and CV mortality (HR 0.47 vs. 0.26) in both males and females, respectively (p-interaction 0.20 and 0.11). Conclusions: We demonstrate important sex differences in CVH metrics along with notable variations based on age and race/ethnicity. Furthermore, we highlight that CVH metrics including health factors and health behaviors are associated with mortality in both females and males. These findings underscore the importance of designing and implementing effective strategies for both sexes, aimed at targeting these specific factors.